ANALISIS PENGARUH DESAIN PRODUK DAN KINERJA SUPPLY CHAIN MANAGEMENT DALAM MENCIPTAKAN KEUNGGULAN BERSAING (Studi Pada Usaha Mikro Olahan Bandeng di Kota Semarang) - Muhamad Ali Akbar; Retno Hidayati (Faculty of Economics and Business Diponegoro University, 2022)
Companies in the era of globalization are required to be able to adapt to an environment with relatively fast changes that are uncontrollable and face increasingly competitive competition. Seeing these conditions, this study aims to analyze product design and supply chain management performance on competitive advantage in MSME Processed Milkfish in Semarang City. The population used in this study is the owner or leader of Milkfish Processed Micro Enterprises (UMKM) in Semarang City which has been established for at least 3 months. The number of samples used in this study were 150 respondents. The method of data collection is done by questionnaire. The data that has been collected is processed and analyzed using the Structural Equation Modeling (SEM) analysis technique with AMOS 24.0 analysis tool. The results of this study indicate that supply chain management performance has a positive and significant effect on competitive advantage, product design has a positive and significant effect on competitive advantage, product design has a positive and significant effect on supply chain management performance.